Task effects in children's word recall: Expanding the reverse production effect. - López Assef, Belén; Zamuner, Tania (Journal of Child Language, 2026)
Words said aloud are typically recalled more than words studied under other techniques. In certain circumstances, production does not lead to this memory advantage. We investigated the nature of this effect by varying the task during learning. Children aged five to six years were trained on novel words which required no action (Heard) compared to Verbal-Speech (production), Non-Verbal-Speech (stick out tongue), and Non-Verbal-Non-Speech (touch nose). Eye-tracking showed successful learning of novel words in all training conditions, but no differences between conditions. Both non-verbal tasks disrupted recall, demonstrating that encoding can be disrupted when children perform different types of concurrent actions.